Program Development and Learning Evaluation (MeDiVA) for Slow Learning Students of the Primary School Teacher Education Study Program - Hayu, Wiworo Retnadi Rias; Dhania, Hanrezi; Prasetyo, Teguh; Rasmitadila, Rasmitadila; Amril, Laode (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
Learning innovation is very important to develop to support effective implementation. Slow learner students need student media and evaluations that make it easier to understand lecture material. So far, researchers have not found any media that helps slow learner students in inclusive education courses. This research aims to produce and develop MEDIVA products for slow learning PGSD students. This development uses a 4D model (Define, Design, Development and Dissemination). The results of this research are research and development carried out using a 4D model, the initial stage or needs analysis stage is carried out by analyzing the basic problems that exist in the learning process, the design stage is creating an Android-based application. designing learning media using a storyboard framework, the development stage is developing Android-based learning media applications, then validation is carried out by material and media experts. The validation results show that in terms of material it is valid, suitable for use with revisions. In terms of media, it is valid, suitable for use with revision. Next, conducting a limited trial (implementation), at the limited trial stage, 21 students including 2 slow learners gave very good responses and carried out evaluations by revising the product according to expert input. Based on the research results, it can be concluded that MEDIVA based on the Android application is declared valid, feasible, easy to use and interesting to use